Establishing an institutional therapeutic apheresis registry. Issue 6 (23rd January 2016) - Mann, Steven A.; McCleskey, Brandi; Marques, Marisa B.; Adamski, Jill
Abstract : Apheresis was first performed as a therapeutic procedure in the 1950s. The first national therapeutic apheresis (TA) registry was established in Canada in 1981 and other national registries followed, including two attempts at establishing an international TA registry. There is no national registry in the United States. Our large, academic, tertiary hospital has a very active TA service. We created a TA database to track all procedures performed by the apheresis service by transferring data from paper appointment logs and the electronic medical records into a Microsoft Access database. Retrospective data from each TA procedure performed at UAB from January 1, 2003 through December 31, 2012 were entered, including the type of procedure, indication, date, and patient demographics. Microsoft Excel was used for data analysis. During the 10‐year period, our TA service treated 1, 060 patients and performed 11, 718 procedures. Of these patients, 70% received therapeutic plasma exchange (TPE), 21% received extracorporeal photopheresis (ECP), 4.5% received red cell exchange (RCE), 4.2% received leukocytapheresis, and 0.6% underwent platelet depletion. Among the procedures, 54% were TPEs, 44% were ECPs, 1.3% were RCEs, 0.5% were leukocytaphereses, and 0.1% were platelet depletions. According to the current literature, national and international TA use is underreported. We believe that the UAB TA registry provides useful information about TA practices in our region and can serve as a model for other institutions. Furthermore, data from multiple institutional registries can be used for clinical research to increase the available evidence for the role of TA in various conditions. J. Clin. Apheresis 31:516–522, 2016. © 2015 Wiley Periodicals, Inc.